Multilayer Mie Scattering Model for Investigation of Intracellular Structural Changes in the Nucleolus and Cytoplasm - S. Saltsberger; I. Steinberg; I. Gannot (International Journal of Optics)
Light scattering from biological cells has been used for many years as a diagnostic tool. Several simulation methods of the scattering process were developed in the last decades in order to understand and predict the scattering patterns. We developed an analytical model of a multilayer spherical scattering cell. Here, we describe the model and show that the results obtained within this simple method are similar to those obtained with far more complicated methods such as finite-difference time-domain (FDTD). The multilayer model is then used to study the effects of changes in the distribution of internal cell structures like mitochondria distribution or nucleus internal structures that exist in biological cells. Such changes are related with cancerous processes within the cell as well as other cell pathologies. Results show the ability to discriminate between different cell stages related to the mitochondria distributions and to internal structure of the nucleolus.